Cédric Andrieux: With Bel, Benjamin, and Brecht in Vancouver - Dickinson, Peter (TDR (1988-), 2014)
A Vancouver performance of the fifth and final installment in Jérôme Bel's series of talking dance portraits prompts some critical reflections on the choreographer's Benjaminian excavation and Brechtian exposition of how the life of a Merce Cunningham dancer intersects with the larger institutionalized history of dance.
https://katalog.adlr.link/Record/ai-55-aHR0cDovL3d3dy5qc3Rvci5vcmcvc3RhYmxlLzI0NTg0ODIx